2019
DOI: 10.7717/peerj.8132
|View full text |Cite
|
Sign up to set email alerts
|

Design and preliminary application of affinity peptide based on the structure of the porcine circovirus type II Capsid (PCV2 Cap)

Abstract: BackgroundAffinity peptides, as a core part of affinity chromatography, play an important role in the purification of target molecules.MethodsHere we describe the use of molecular docking technology for virtual screening of affinity peptides that specifically recognize the PCV2 Cap protein for the first time. Thirteen candidate peptides with high scores were obtained and then further characterized. Experimentally, the affinity and sensitivity of the peptides studied were identified by ELISA and LSPR, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…After the virus enters the host cell, it replicates itself with the host’s help and threat ( Hao et al, 2019 ). Viruses seek advantages, avoid disadvantages, and also affect the internal environment of host cells.…”
Section: Discussionmentioning
confidence: 99%
“…After the virus enters the host cell, it replicates itself with the host’s help and threat ( Hao et al, 2019 ). Viruses seek advantages, avoid disadvantages, and also affect the internal environment of host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since S2 subunit performs an important role in viral infusion and entry, it is also more conserved to be the target site for anti-viral inhibitor development ( Ng and Mohd-Ismail, 2021 ). Our data showed that Spep-1 had a high affinity to SARS-CoV-2 spike trimer and monomer protein, with the K D values of 1.70 and 2.14 nmol/L (Spep-1 as the ligand in SPR analysis), which are quite high among the reported peptides ( Mendoza-Figueroa et al, 2018 ; Hao et al, 2019 ; Pomplun et al, 2021 ; Rosestedt et al, 2021 ), suggesting that Spep-1 may have good application prospects, not only limited to SARS-CoV-2 spike antigen detection. In future studies, with rational modifications, Spep-1 might be used for studying the spatial and temporal distribution of S2 subunit during virus infusion, in vivo virus tracing, and drug delivery in biosafety laboratories.…”
mentioning
confidence: 71%
“…21 Yang (K D = 49.4 nM) 43 observed kinetics binding by using sdAb. Hao (K D = 103 nM) 39 and Zheng (K D = 98.5 nM) 38 observed kinetics binding using peptides against PCV2. However, no report has evaluated the binding affinity of the scFv antibody to PCV2 using SPR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Phage display screening has previously been used for selecting the specific binder to the PCV2 capsid, but different libraries exist such as peptide libraries and Bactrian camel sdAb library. This study used human scFv library. The single-domain antibody (sdAb) has smaller fragments with size 15 kDa consisting of either VH or VL domains, while scFv consists of both VH and VL with a size of 28 kDa.…”
Section: Discussionmentioning
confidence: 99%